Triplet-encoded prebiotic RNA aminoacylation - Su, Meng; Schmitt, Christian; Liu, Ziwei; Roberts, Samuel J.; Liu, Kim C.; Röder, Konstantin; Jäschke, Andres; Wales, David J.; Sutherland, John D. (Journal of the American Chemical Society, 2023)
The encoding step of translation involves attachment of amino acids to cognate tRNAs by aminoacyl-tRNA synthetases, themselves the product of coded peptide synthesis. So, the question arises─before these enzymes evolved, how were primordial tRNAs selectively aminoacylated? Here, we demonstrate enzyme-free, sequence-dependent, chemoselective aminoacylation of RNA. We investigated two potentially prebiotic routes to aminoacyl-tRNA acceptor stem-overhang mimics and analyzed those oligonucleotides undergoing the most efficient aminoacylation. Overhang sequences do not significantly influence the chemoselectivity of aminoacylation by either route. For aminoacyl-transfer from a mixed anhydride donor strand, the chemoselectivity and stereoselectivity of aminoacylation depend on the terminal three base pairs of the stem. The results support early suggestions of a second genetic code in the acceptor stem.
Online verfügbar: 12. Juli 2023
Gesehen am 21.08.2023